2014
DOI: 10.1104/pp.114.251371
|View full text |Cite
|
Sign up to set email alerts
|

Dual Catalytic Activity of Hydroxycinnamoyl-Coenzyme A Quinate Transferase from Tomato Allows It to Moonlight in the Synthesis of Both Mono- and Dicaffeoylquinic Acids

Abstract: Tomato (Solanum lycopersicum), like other Solanaceous species, accumulates high levels of antioxidant caffeoylquinic acids, which are strong bioactive molecules and protect plants against biotic and abiotic stresses. Among these compounds, the monocaffeoylquinic acids (e.g. chlorogenic acid [CGA]) and the dicaffeoylquinic acids (diCQAs) have been found to possess marked antioxidative properties. Thus, they are of therapeutic interest both as phytonutrients in foods and as pharmaceuticals. Strategies to increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 43 publications
(60 reference statements)
2
59
0
2
Order By: Relevance
“…Incubation of caffeoyl shikimate with buffer alone, or with enzyme extracts with low CSE activity, resulted in the appearance of a new compound with lower retention time but identical UV spectrum to the initial substrate. Initially, we thought that this compound might be an additional ester of shikimate, formed either by trans‐esterification (Petersen, ) or possibly through additional activity of HCT; this latter type of reaction has recently been reported for formation of dicaffeoyl quinate (Vanholme et al ., 2013a; Moglia et al ., ). However, MS analysis indicated that the compound could not be a dicaffeoyl ester, and, because it is formed in the absence of enzyme, it is probably an adduct formed by reaction with a component in the buffer.…”
Section: Discussionmentioning
confidence: 97%
“…Incubation of caffeoyl shikimate with buffer alone, or with enzyme extracts with low CSE activity, resulted in the appearance of a new compound with lower retention time but identical UV spectrum to the initial substrate. Initially, we thought that this compound might be an additional ester of shikimate, formed either by trans‐esterification (Petersen, ) or possibly through additional activity of HCT; this latter type of reaction has recently been reported for formation of dicaffeoyl quinate (Vanholme et al ., 2013a; Moglia et al ., ). However, MS analysis indicated that the compound could not be a dicaffeoyl ester, and, because it is formed in the absence of enzyme, it is probably an adduct formed by reaction with a component in the buffer.…”
Section: Discussionmentioning
confidence: 97%
“…We envision that the NADP + ‐dependent QDHs produce quinate in the chloroplast, which is then transported to the cytoplasm where it condenses with hydroxycinnamic acids to form CGA. It is established that the HQT involved in CGA biosynthesis is localized in the cytoplasm and vacuoles (Moglia et al ., ). We expect this process to be more actively occurring during the early stages of plant growth and development, because an actively growing plant requires a constant supply of CGA as an antioxidant and protection from UV light, herbivory and microbial pathogens (Mondolot et al ., ; Wojciechowska et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Quinate is a precursor for the biosynthesis of chlorogenic acids (CGAs) in plants (Cle et al ., ; Moglia et al ., ). Chlorogenic acids accumulate in leaves and fruits where they act as feeding deterrents and antifungal agents.…”
Section: Introductionmentioning
confidence: 97%
“…This enzyme usually displayed a substrate preference for shikimate. In tomato, the HQT catalysed the formation of chlorogenic acid from caffeoyl-CoA and quinic acid at neutral pH, but the formation of 3,5-dicaffeoylquinic acid from chlorogenic acid at lower pH (Moglia et al 2014). Further studies have shown that this enzyme has a dual localisation and is active as HQT in the cytosol and as chlorogenate:chlorogenate hydroxycinnamoyltransferase (CCT) in the vacuole.…”
Section: Eccs Ecbahd8mentioning
confidence: 97%